Factors influencing ambulance nurses' adherence to a national protocol ambulance care: an implementation study in the Netherlands. (June 2015) - Ebben, Remco H.A.; Vloet, Lilian C.M.; van Grunsven, Pierre M.; Breeman, Wim; Goosselink, Ben; Lichtveld, Rob A.; Mintjes-De Groot, Joke A.J.; van Achterberg, Theo
Abstract : Objectives: Adherence to prehospital guidelines and protocols is suboptimal. Insight into influencing factors is necessary to improve adherence. The aim of this study was to identify factors that influence ambulance nurses' adherence to a National Protocol Ambulance Care (NPAC). Methods: A questionnaire was developed using the literature, a questionnaire and expert opinion. Ambulance nurses ( n =452) from four geographically spread emergency medical services (EMSs) in the Netherlands were invited to fill out the questionnaire. The questionnaire included questions on influencing factors and self-reported adherence. Results: Questionnaires were returned by 248 (55%) of the ambulance nurses. These ambulance nurses' adherence to the NPAC was 83.4% (95% confidence interval 81.9–85.0). Bivariate correlations showed 23 influencing factors that could be related to the individual professional, organization, protocol characteristics and social context. Multilevel regression analysis showed that 21% of the variation in adherence ( R 2 =0.208) was explained by protocol characteristics and social influences. Conclusion: Ambulance nurses' self-reported adherence to the NPAC seems high. To improve adherence, protocol characteristics (complexity, the degree of support for diagnosis and treatment, the relationship of the protocol with patient outcomes) and social influences (expectance of colleagues to work with the national protocol) should be addressed.